Os usos do salão de beleza : para além do consumo de estética ou sobre possibilidades de invenção de si - Pupa, Iorrana Fioreti de Menezes (2012)
In the contemporaneous context, the act of consuming has been a subject of great interest by researchers from different areas. It has been approached from diversified perspectives, based on production process or social argument. This research, originated